Thermal analysis study of solid-phase synthesis of zinc- and titanium-substituted lithium ferrites from mechanically activated reagents; Journal of Thermal Analysis and Calorimetry; Vol. 122, iss. 3 - Lysenko E. N. Elena Nikolaevna; Surzhikov A. P. Anatoly Petrovich; Vlasov V. A. Vitaliy Anatolievich; Malyshev A. V. Andrei Vladimirovich; Nikolaev E. V. Evgeny Vladimirovich (2015, 2015)
Title screen